GBAAM : group-based access authentication for MTC in LTE networks - Cao, Jin (2015)
Machine Type Communication (MTC), as one of the most important communication approaches in the future mobile communication, has drawn more and more attention. To meet the requirements of low power consumption of devices and mass device transmission is the key issue to achieve MTC applications security in the Long Term Evolution (LTE) networks. When a large number of MTC devices simultaneously connect to the network, each MTC device needs to implement an independent access authentication procedure in the current third Generation Partnership Project (3GPP) standard, which will cause a severe signaling congestion in the LTE network. In this paper, we propose a group-based access authentication scheme, by which a good deal of MTC devices can be simultaneously authenticated by the network and establish an independent session key with the network respectively. Our scheme cannot only greatly reduce the signal transmission for mass of devices to the network and thus avoid the signaling overload over the LTE network, but also achieve robust security including Key Forward/Backward Secrecy (KFS/KBS) and non-repudiation verification. The experimental results and formal verification by using the TLA+ and TLC show that the proposed scheme is secure against various malicious attacks.